63*73-63*63简便算法

125*25*64 72*26+36*48

第1个回答  2011-05-08
63*73-63*63
=63x(73-63)
=63x10
=630

125x25x64
=125x25x8x4x2
=(125x8)x(25x4)x2
=1000x100x2
=200000

72x26+36x48
=36x2x26+36x48
=36x(52+48)
=36x100
=3600本回答被提问者采纳
第2个回答  2011-05-08
可怜的孩子,肯定是上课没有听讲

简便算法的一些窍门

找公约数、
凑整 法
补数 法 等

22+78=100   36+64=100 43+57 =100 
4*25  8*125
第3个回答  2011-05-08
第一个 原式=63×(73-63)=63×10=630
第二个 原式=(125×8)×(4×25)×2=1000×100×2=200000
第三个 原式=36×52+36×48=36×(52+48)=36×100=3600
第4个回答  2011-05-08
63*73-63*63=63*(73-63)=63*10=630
125*25*64=125*25*4*8*2=125*8*25*4*2=1000*100 *2=200000
72*26+36*48=36*2*26+36*48=36*(52+48)=36*100=3600
第5个回答  2011-05-08
63*73-63*63
=63*(73-63)
=63*10
=630

125*25*64
=125*8*25*8
=1000*200
=200000

72*26+36*48
=36*52+36*48
=36*(52+48)
=36*100
=3600